Creep and shrinkage of high strength concrete - Pisarn Siripatt; Yamamoto, Yasuhiko; Kawaguchi, Masahiro; Worsak Kanok-Nukulchai; The Canadian Government (Bangkok : Asian Institute of Technology, 1979)
The main purpose of this work is to examine the magnitudes of creep and shrinkage of various concretes. Concretes of four different strengths were used for this purpose. Their target strengths at 28 day age were 30, 50, 65 and 80 N/mm2. The specimens were cured in a fog room for about 35 days and were, then, tested for creep and shrinkage for 120 days. The test were performed in the room where temperature and humidity were controlled at (22 ± 2)0c and 80% R.H. , respectively, Following are the main findings. 1. Creep and shrinkage of higher strength concrete were smaller compared with those of lower strength concrete. 2. A linear r elation between creep and stress- strength ratio exists also in the case of very high strength concrete if the stress- strength ratio is less than 40%. 3. The smaller creep and shrinkage of higher strength concrete can be explained by the existence of smaller amount of hydration products which are responsible for the creep and shrinkage.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology,1979
Keywords: Creep of concrete; Concrete -- Expansion and contraction